(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2019)
This research aims to ensure the launch of Interactive Television (ITV) as a new product in the television market, securing the best Net Present Value (NPV) that guarantees the initial implementation investment through the best forecasting. Specialists project market growth from 2015 onwards at 50,000 households with television per year, expecting to reach 3,450,000 households by 2020 with an NPV of 63,883,374 for an initial investment of 110,000,000. This forecast is adjusted by the Crystal Ball (CB) simulator to 3,295,768 households consuming television in the projected year 2015 up to 3,581,193 by 2020, with a net NPV of 73,715,279 using the same discount rate of 10%. The process simulates 12,500 trials, achieving a 95% confidence level, which was reached in just 12,437 trials. With the new product (ITV) inserted into the market, sensitivity analysis shows that ITV will contribute 28.8% to the Net Present Value by 2020, and as expected, the negative contribution of the initial investment accounts for a 13.7% reduction in the NPV. The new Net Present Value increases by approximately ten million as a result of the simulated quantitative process.